2020
DOI: 10.1016/j.pharmthera.2019.107430
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy as a novel therapeutic target in vascular calcification

Abstract: 2. Is it all necessary or can some of it be deleted as 'off topic' (examples)?As mentioned above it would be important to follow VSMC calcification rather than a mixture of very different disease entities. I still believe that media sclerosis and arteriosclerosis are very different diseases. Authors' response:We thank the reviewer for highlighting this point. We agree with the reviewer that media sclerosis and arteriosclerosis are very different diseases, although they may share some similar common mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 130 publications
2
55
0
1
Order By: Relevance
“…In turn, induced apoptosis generates oxidative stress, further mitochondrial dysfunction, apoptotic bodies, and MVs [135][136][137][138], events that have been mechanistically linked to DNA damage, ER stress, autophagy or mitophagy, and calcium phosphate deposition. It can also induce osteogenic gene induction and transformation into osteogenic phenotype of VSMCs [139][140][141][142]. Apoptosis is not mutually exclusive, but actually complementary to other pathways introduced in this review that eventually lead to VC.…”
Section: Apoptosismentioning
confidence: 82%
“…In turn, induced apoptosis generates oxidative stress, further mitochondrial dysfunction, apoptotic bodies, and MVs [135][136][137][138], events that have been mechanistically linked to DNA damage, ER stress, autophagy or mitophagy, and calcium phosphate deposition. It can also induce osteogenic gene induction and transformation into osteogenic phenotype of VSMCs [139][140][141][142]. Apoptosis is not mutually exclusive, but actually complementary to other pathways introduced in this review that eventually lead to VC.…”
Section: Apoptosismentioning
confidence: 82%
“…Autophagy is commonly regarded as a protective mechanism against vascular calcification 11 , but its activity in this role is controversial. Several studies have suggested an increase in autophagic flux and the formation of autophagic vesicles during the calcification process 11 , whereas other investigators have identified that autophagic flux is defective 4,[12][13][14] . These discrepancies may be caused by differences in cell types, assay conditions, or methods to measure autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…At pathogenic and clinical levels, vascular calcification shares many similarities with bone formation, and its severity is commonly accompanied by a heightened risk of cardiovascular events and all-cause mortality; however, no therapeutics are currently available. Multiple cardiovascular-related cells, including endothelial cells, pericytes, vascular smooth muscle cells (VSMCs) and valve interstitial cells, are involved in vascular calcification, and among these, VSMCs are the predominant cell type involved, having biosynthetic, proliferative and contractile roles in the vessel wall 3,4 . Continuous intracellular or environmental stimuli, including oxidative stress, hypoxia, abnormal mineral metabolism, apoptosis and chronic inflammation, contribute to a phenotypic change of VSMCs to osteoblast-like cells, in which master transcription factors of osteogenesis and chondrogenesis are upregulated concomitant with the generation of mineralized extracellular matrix; parallel with this process, VSMCs lose a range of contractile proteins, eventually causing vascular calcification 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of mitophagy might restore mitochondrial function. [67] Highconcentration phosphate could promote the production of mitochondrial superoxide anion and then activate the autophagy of VSMCs. When autophagy was suppressed, the calcium deposition was increased and VSMCs released more MVs and EVs, which contained high ALP activity and accelerated the development of VC.…”
Section: Mitochondria Affect Vc Directly By Oxidative Stress Damagementioning
confidence: 99%
“…[106] In addition, the autophagy process could also maintain the mitochondrial homeostasis to regulate calcification process. [107] With the maturation of gene-editing technology, there were more increasing studies on the root of diseases, so in the future, the regulation of mtDNA stability or even directly affecting POLG might be a potential therapeutic target. Therefore, some measures point to mitochondria might also be a novel insight into VC.…”
Section: Application and Prospectmentioning
confidence: 99%